Metode Biblioterapi dan Diskusi Dilema Moral untuk Pengembangan Karakter Tanggungjawab - Dewi, Noviana; Prihartanti, Nanik (Faculty of Psychology, Universitas Gadjah Mada, 2014)
This research aimed to know the effects of the methods of bibliotherapy and discussion on the moral dilemmas in enhancing responsible character. The subjects of the research were 65 students of â€œANâ€ divided into three groups; bibliotherapy experimental group, moral discussion experimental group, and non-treatment control group. The research used pretest-posttest-follow-up design. The data of this experimental research were obtained by using a scale of responsible character consisting of aspects of self-control skill, risk-taking for personal choice and seriousness of doing obligation to others. The data were then analyzed using the SPSS.19 software program. The analyzed factors indicated that there were five dimensions shaping studentsâ€™ responsible character, namely carefulness, task-oriented, excellence, perseverance, and commitment. Based on the hypothesis test through a one-way ANOVA technique, it was concluded that the two methods have an effect on the enchancement of studentsâ€™ responsible character.